2001
DOI: 10.1007/s004170100366
|View full text |Cite
|
Sign up to set email alerts
|

Influence of refractive correction on peripheral visual field in static perimetry

Abstract: A significant association between refractive errors and differential light sensitivity exists in the peripheral visual field of myopic eyes. Therefore, contact lens wear is recommended when performing automated perimetry of the peripheral visual field of myopic patients with higher refractive errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…(1) appraisal of the hill of vision at each test location of the stimulus grid individually (Goldmann 1945;Brenton & Phelps 1986;Iwase et al 1988;Zulauf et al 1994a;Koller et al 2001), disregarding the correlation between neighbouring points (Lachenmayr et al 1995), or (2) introduction of VF indices for the averaging of threshold values over certain VF areas (Haas et al 1986;Katz & Sommer 1986;Lachenmayr et al 1994;Zulauf et al 1994b), disregarding local characteristics of the VF.…”
Section: Discussionmentioning
confidence: 99%
“…(1) appraisal of the hill of vision at each test location of the stimulus grid individually (Goldmann 1945;Brenton & Phelps 1986;Iwase et al 1988;Zulauf et al 1994a;Koller et al 2001), disregarding the correlation between neighbouring points (Lachenmayr et al 1995), or (2) introduction of VF indices for the averaging of threshold values over certain VF areas (Haas et al 1986;Katz & Sommer 1986;Lachenmayr et al 1994;Zulauf et al 1994b), disregarding local characteristics of the VF.…”
Section: Discussionmentioning
confidence: 99%
“…Refractive errors of the subjects included in this study ranged between –8 and +8 dpt. Such refractive errors never influence the isopter positions outside the central 30° of the visual field [7, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…Other factors significantly influencing the outcome of the visual field testing include refractive errors [3], also outside the central 30º of the visual field [7, 8], pupil size, medium opacities, eyelid and nose effects, spectacle-lens effects, cooperation, examiner and learning effects [3, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Koller et al 19 suggested that in the peripheral VFs (outside the central 301), refractive errors have a minor influence on the decrease of the differential light sensitivity because of significant spatial summation through the relatively greater contribution of rods. However, this 'minor influence' was not quantified, and the study in question 19 only examined the peripheral VFs between 30 and 501 from fixation.…”
Section: Discussionmentioning
confidence: 99%